Online Premarital School Trends towards Digital Transformation in Family Law Education - Salsabila, Sabrina Rahmah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This paper explores the trend of online premarital schools and their digital transformation in the context of family law education in Indonesia. Premarital schools promote Islamic family law thinking that provides guidelines for ideal family relationships. The development of premarital schools can be a requirement for marriage registration outside of marriage guidance organized by the Ministry of Religion. With various digitalization innovations, online premarital schools have been developed. Interestingly, the public's enthusiasm for participating in online premarital schools is very high. The focus of this study is to reveal the trend of online premarital schools that are developing in Indonesia and how digital transformation in family law education is developed in online premarital schools. Using qualitative methods, researchers trace the innovations and attractions developed by several digital-based premarital school organizers. The findings are that the Salman ITB Online Premarital School, Nurul Ashri Premarital School, and Sunnah Marriage Camp Deen Academy have existed and developed in Indonesia. The shift from conventional premarital education to online is based on accessibility, namely the ease of access to information by utilizing digital platforms as learning media. Flexibility in the process of interaction and adaptation of online premarital school technology has facilitated the transfer of family law knowledge. The next finding is the family law education facility in the form of e-learning so that all its benefits can be felt online.